2008
DOI: 10.1021/ac801048g
|View full text |Cite
|
Sign up to set email alerts
|

Impedance Biosensor for Peanut Protein Ara h 1

Abstract: A reagentless electrochemical impedance biosensor for detection of peanut protein Ara h 1, one of the allergenic proteins found in peanuts, has been demonstrated using an Au substrate onto which an antibody film has been immobilized. Following initial stabilization of the self-assembled monolayer (SAM) through which the antibody is immobilized, the biosensor substrate exhibits stable impedance spectra at different stages of substrate preparation. By fitting the impedance spectra to a Randles equivalent circuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(71 citation statements)
references
References 42 publications
3
67
0
1
Order By: Relevance
“…In comparison with other published immunosensors for the analysis of Ara h 1 (Huang et al, 2008;Pollet et al, 2011), the major drawback of the developed immunosensor is the analysis time (3 h 50 min); Huang et al (2008) and Pollet et al (2011) reported analysis times of 5 min and 20 min, respectively. However, this drawback is largely overcome by the wider calibration range (25-2000 ng/ml) and much lower LOD (3.8 ng/ml) obtained in this work when compared to the ones obtained by Huang et al (2008) (20-240 ng/ml, o20 ng/ml) and Pollet et al (2011) (100-2000 ng/ml, 90 ng/ml). Furthermore, Huang et al (2008) did not report the analysis of samples; therefore the utility of the developed sensor is not fully proven.…”
Section: Methods Validationmentioning
confidence: 90%
See 2 more Smart Citations
“…In comparison with other published immunosensors for the analysis of Ara h 1 (Huang et al, 2008;Pollet et al, 2011), the major drawback of the developed immunosensor is the analysis time (3 h 50 min); Huang et al (2008) and Pollet et al (2011) reported analysis times of 5 min and 20 min, respectively. However, this drawback is largely overcome by the wider calibration range (25-2000 ng/ml) and much lower LOD (3.8 ng/ml) obtained in this work when compared to the ones obtained by Huang et al (2008) (20-240 ng/ml, o20 ng/ml) and Pollet et al (2011) (100-2000 ng/ml, 90 ng/ml). Furthermore, Huang et al (2008) did not report the analysis of samples; therefore the utility of the developed sensor is not fully proven.…”
Section: Methods Validationmentioning
confidence: 90%
“…There are very few publications regarding the development of biosensors for the specific detection of Ara h 1, namely using surface plasmon resonance (SPR) (Pollet et al, 2011;Tran et al, 2013) and electrochemical impedance spectroscopy (EIS) (Huang et al, 2008;Singh et al, 2010;Sun et al, 2012) for detection purposes. Huang et al (2008), Singh et al (2010) and Pollet et al (2011) used immunoassays whereas Sun et al (2012) and Tran et al (2013) used DNA-based recognition elements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, comparison is possible with immunosensors that have been developed to detect other peanut allergens. For example, Singh et al [17] and Huang et al [18] described two impedimetric immunosensors for Ara h 1 detection with LODs of 40 ng/ml and <0.3 nM (<19 ng/ml), respectively. Pollet et al [15] developed an optical biosensor for Ara h 1 with an LOD of 90 ng/ml, and Mohammed et al [26] developed an optical immunosensor able to detect 0.7 μg of peanut allergens/ml of extract.…”
Section: Methods Validationmentioning
confidence: 99%
“…Although there are some devices (immuno-and genosensors) described for the detection of some peanut allergens (e.g., Ara h 1, Ara h 3) [15][16][17][18][19], to the best of our knowledge, a biosensor for the specific detection of Ara h 6 was not described up to date.…”
Section: Introductionmentioning
confidence: 99%